New Mediterranean Biodiversity Records (April, 2014) - K. KAPIRIS; C. APOSTOLIDIS; R. BALDACCONI; N. BAŞUSTA; M. BILECENOGLU; G. BITAR; D.C. BOBORI; Y.Ö BOYACI; C. DIMITRIADIS; M. DJUROVIĆ; J. DULČIĆ; F. DURUCAN; et al. (Mediterranean Marine Science, 2014)
According to reports, the following 16 species have extended their distribution to other Mediterranean areas or have made a new appearance in other regions. The first category includes the following organisms: The rare and common Indo-Pacific seaweed Codium arabicum (Lebanese coasts), the acari Thalassarachna affinis (Marmara Sea), and the non-indigenous nudibranch Flabellina rubrolineata, which has also been found in many other areas of the Aegean Sea. In addition, the rare sea slug Thecacera pennigera (Piccolo of Taranto), the fangtooth moray Enchelycore anatina (National Marine Park of Zakynthos, Ionian Sea), the carangid Seriola fasciata (Gulf of Antalya), Lagocephalus sceleratus (SE. Ionian Sea), the reticulated leatherjacket Stephanolepis diaspros (Slovenia, N. Adriatic Sea), the marbled stingray, Dasyatis marmorata (NE Levantine), the starry smooth-hound Mustelus asterias (Iskenderun Bay, NE Mediterranean), the cephalopod Ommastrephes bartramii (Ionian Sea) have also been reported. The Atlantic crab Dyspanopeus sayi has expanded to many Italian areas and the blue crab Callinectes sapidus to a lake in N. Greece and in the S. Adriatic Sea. Finally, Farfantepenaeus aztecus has been found in the Ionian Sea, thus showing its wide expansion in the Mediterranean. The larval stages of Faccionella oxyrhyncha have been found, after many years, in the Aegean Sea and the first report of an existence on intersexual acari Litarachna duboscqi in Split(Adriatic Sea) was reported.

New Mediterranean Marine biodiversity records (December, 2013) - M. BILECENOGLU; J.E.F. ALFAYA; E. AZZURRO; R. BALDACCONI; Y.Ö. BOYACI; V. CIRCOSTA; L.J.V. COMPAGNO; F. COPPOLA; A. DEIDUN; H. DURGHAM; F. DURUCAN; D. ERGÜDEN; et al. (Mediterranean Marine Science, 2013)
Based on recent biodiversity studies carried out in different parts of the Mediterranean, the following 19 species are included as new records on the floral or faunal lists of the relevant ecosystems: the green algae Penicillus capitatus (Maltese waters); the nemertean Amphiporus allucens (Iberian Peninsula, Spain); the salp Salpa maxima (Syria); the opistobranchs Felimida britoi and Berghia coerulescens (Aegean Sea, Greece); the dusky shark Carcharhinus obscurus (central-west Mediterranean and Ionian Sea, Italy); Randall’s threadfin bream Nemipterus randalli, the broadbanded cardinalfish Apogon fasciatus and the goby Gobius kolombatovici (Aegean Sea, Turkey); the reticulated leatherjack Stephanolepis diaspros and the halacarid Agaue chevreuxi (Sea of Marmara, Turkey); the slimy liagora Ganonema farinosum, the yellowstripe barracuda Sphyraena chrysotaenia, the rayed pearl oyster Pinctada imbricata radiata and the Persian conch Conomurex persicus (south-eastern Crete, Greece); the blenny Microlipophrys dalmatinus and the bastard grunt Pomadasys incisus (Ionian Sea, Italy); the brown shrimp Farfantepenaeus aztecus (north-eastern Levant, Turkey); the blue-crab Callinectes sapidus (Corfu, Ionian Sea, Greece). In addition, the findings of the following rare species improve currently available biogeographical knowledge: the oceanic pufferfish Lagocephalus lagocephalus (Malta); the yellow sea chub Kyphosus incisor (Almuñécar coast of Spain); the basking shark Cetorhinus maximus and the shortfin mako Isurus oxyrinchus (north-eastern Levant, Turkey).

Sexual reproduction, larval development and release in Spongia officinalis L. (Porifera, Demospongiae) from the Apulian coast - R. Baldacconi; C. Nonnis-Marzano; E. Gaino; G. Corriero (Marine Biology, 2007)